An Analysis of Corporate Taxpayers’ Perception of Covid-19 Tax Incentives - Jauhari, Zaidan; Soepriyanto, Gatot (Indonesian Journal of Multidisciplinary Science, 2023)
Covid-19 has decreased the level of consumption or people's purchasing power and various domestic industrial sectors have been affected. The difficulties that occurred in these various sectors then encouraged the government to carry out economic recovery by implementing various policies, both fiscal, monetary and financial policies. One of the fiscal policies pursued is through statutory regulatory instruments through the Minister of Finance Regulation. The research was conducted at the East and North Kalimantan Regional Offices of the Directorate General of Taxes, specifically in KPP Pratama Samarinda Ilir, KPP Pratama Samarinda Ulu, and KPP Pratama Tenggarong. Researchers took three general answers from the answers of all respondents. The respondents' answers illustrate that the socialization related to tax incentives is not well known by taxpayers. Many taxpayers tend to think that this socialization is not important, so they do not follow it. There are those who also think that it does not really help them in administration. Information related to tax incentives is not fully known by taxpayers and the lack of tax information obtained. The quality of service received by taxpayers is classified as satisfactory and good and simple. Taxpayer behavior is still not supportive as can be seen from the low level of awareness. Taxation socialization has been carried out by the DGT, but the level of participation of taxpayers in this socialization is still low. Tax incentives for the Covid-19 pandemic have been underutilized, due to the opinion of taxpayers that the amount of incentives received is too small.